Bío-Bío Regional Theater: body, space and movement - Barría Chateau, Hernán (2018)
The Bío-Bío Regional Theater was recently inaugurated in the city of Concepción,Chile. Located on the riverbank, it is a rectangular building, with an oblong floor and surrounded by a perimeter membrane, which illuminates revealing a spatial grid of reinforced concrete. A naked skeleton that propagates and projects geometrically in all directions of the central hall of the theater and through a web of lights on the floor of the public atrium that precedes it. Through a complex reading, a series of conceptual images is revealed that support the experimental model of theater and, ultimately, its architecture and language.